The response of mangrove degradation to mineral composition - Zhao, Lintao; Chen, Dezhi; Tan, Haoyuan; Wang, Yingjing; Qiao, Ying; Xing, Yongze (Frontiers in Marine Science, 2025)
Mangrove wetlands serve as pivotal ecotones at land-sea interfaces, where habitat stability is critically modulated by sediment mineralogical composition. However, the impacts of anthropogenic activities on mineralogical evolution and associated ecological consequences in these ecosystems remain poorly understood. This study examines these processes in a degraded mangrove ecosystem within Tieshangang Bay, China, to uncover engineering-induced perturbations and their implications for mangrove health. Integrated mineralogical analyses were employed, including X-ray diffraction (XRD) and automated mineralogical parameter analysis (MapsMin), to characterize sediment composition and discern anthropogenic influences. These techniques enabled high-resolution quantification of mineral distributions and associations across degraded and preserved zones. The results reveal pronounced kaolinite enrichment (48.97–66.35%) in surficial sediments (0–15 cm) of degraded zones, contrasting with stable mineralogical composition in preserved areas. Diagnostic mineral assemblages and spatial patterns implicate terrestrial clay inputs from port infrastructure expansion and dredging operations, exacerbated by tidal channel obstruction and hydrodynamic attenuation. Mechanistic analysis demonstrates that kaolinite’s platy morphology promotes pore occlusion, reducing sediment porosity and inducing rootzone hypoxia, which drives mangrove regression. Based on these findings, a synergistic remediation framework is proposed, integrating tidal hydrology restoration, sediment source regulation, and substrate permeability enhancement. These insights advance the understanding of anthropogenic-geochemical-ecological cascades in intertidal ecosystems and provide a mineralogical benchmark for nature-based mangrove conservation and coastal resilience management.